The software and engineering industries: threatened by technological change? - Goodman, William C. (Monthly Labor Review, 1996)
Part of a special issue on the relationship between computers and employment. Since 1990, employment growth has slowed in the software and engineering industries. Jobs in each of these industries depend, to a large extent, on technological progress. Ironically, technology may also reduce the number of jobs in these industries, as advanced computer tools cut the amount of work required to design a product, be it largely intellectual (as in the case of a software application) or physical (as in the case of an office product, a household appliance, or a new weapon). The writer examines other factors, such as reduced defense expenditure, that have an impact on the number of jobs in the engineering and computer service industries.